Drivers and outcomes of sustainable export marketing strategies in international environments - Silva, G. M.; Dias, Á.; Lisboa, A. C.; Silva, F. P. (Review of International Business and Strategy, 2023)
Export firms are quicker to adopt environmental friendliness than firms focused on domestic markets, due to differences in foreign countries’ environmental requirements. Thus, it is important to understand firms’ green export marketing strategy and its influence on export performance. This study investigates the relationship between market-oriented environmental sustainability and green export-related resources and capabilities; analyzes the impact of these resources and capabilities on the eco-friendly export marketing strategy; and assesses the influence of such strategy on export performance. Using survey data from 241 manufacturing export firms, our study finds a positive influence of market-oriented environmental sustainability on green export-related resources and capabilities. Further, while green export-related capabilities directly affect eco-friendly export marketing strategy, resources only influence it indirectly through capabilities. The results also show that the adoption of an eco-friendly export marketing strategy contributes to firm’s export performance.